PERAN MODERASI UKURAN PERUSAHAAN PADA HUBUNGAN PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN PENGUNGKAPAN CSR - Anindyafebi Tanara; Zaky Machmuddah; St. Dwiarso Utomo (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This research was conducted at the intention of observing and measuring the result of profitability, liquidity and leverage on CSR and company size as a moderating variable. The population taken was 29 manufacturing corporation in the food and beverage area recorded on the IDX in 2018-2021. The sample selection category applied purposive sampling, with a total of 116 samples tested using WarpPLS 7.0 as a research tool. Independent variables include profitability, liquidity, and leverage whereas the dependent variable include CSR and company size as moderating variables. The research results show that ROA and DER have a notable impact on the corporate social explanations. Meanwhile, CR has no impact on the explanation of CSR. Company size could strengthen ROA, CR, and DER in CSR disclosure.Â